Fluoroscopy-assisted posterior percutaneous reduction for the management of unilateral cervical facet dislocations after unsuccessful closed reduction: A case report. (2019) - Shimizu, Takaki; Yoshioka, Katsuhito; Murakami, Hideki; Demura, Satoru; Kato, Satoshi; Yokogawa, Noriaki; Oku, Norihiro; Kitagawa, Ryo; Tsuchiya, Hiroyuki
Highlights: Open reduction of cervical facet dislocation is needed when closed reduction fails. Anterior cervical discectomy and fusion after posterior percutaneous reduction was performed. Posterior percutaneous reduction can be useful for cervical facet dislocations. Abstract: Introduction: In some cases of cervical facet dislocations, open reduction becomes imperative when closed reduction fails. In these cases, posterior open reduction with subsequent posterior fixation has been favored in previous reports as reduction using the posterior approach is less challenging than that using the anterior approach. However, it invades the posterior cervical muscles, is associated with a high risk of postoperative axial neck pain, and is less likely to restore cervical lordosis than anterior surgery. In this report, we describe a novel reduction technique, posterior percutaneous reduction, which can address this dilemma. Presentation of case: An attempt to perform closed reduction in a 19-year-old adolescent with a unilateral facet dislocation at the C4-C5 level was unsuccessful. To preserve the posterior cervical muscles and obtain good cervical alignment, we opted for posterior percutaneous reduction and subsequent anterior cervical discectomy and fusion instead of posterior open reduction and fixation. An elevator was inserted into the locked facet percutaneously with fluoroscopic assistance, and reduction was achieved by lever action. Seven days after the percutaneous reduction, anterior cervical discectomy and iliac bone grafting with plate fixation were performed. There were no complications or neurological deficits postoperatively. Discussion: This report describes the case of a patient who underwent anterior cervical discectomy and fusion after posterior percutaneous reduction with preservation of the posterior cervical muscles for unilateral facet dislocation when closed reduction was unsuccessful. conclusion: Posterior percutaneous reduction could be a useful option for the management of cervical facet dislocations.